Significance of atypical triphasic waves for diagnosing nonconvulsive status epilepticus - (:unkn) unknown (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2007)
The aim of the study described here was to analyze findings in 15 cases who were admitted with nonconvulsive status epilepticus (NCSE) and whose EEGs featured atypical triphasic waves (ATWs). We also investigated whether ATWs are useful for diagnosing this condition. Mental status was assessed, and EEGs were recorded during/after the antiepileptic drug treatment. Eight patients had metabolic disorders and nine had intracranial pathology. The ATWs were unilateral focal in 5 cases and bilaterally asymmetrical focal in 10 cases. In I I of the 15 cases, the ATWs disappeared and mental status improved after treatment. NCSE should be considered in any individual who presents in an acute confusional state and whose EEG reveals either unilateral or bilaterally asymmetric ATWs. (C) 2007 Elsevier Inc. All rights reserved.
Keywords: nonconvulsive status epilepticus; metabolic encephalopathy; atypical triphasic wave; confusional state; electroencephalogram; CONVULSIVE STATUS EPILEPTICUS; COMATOSE PATIENTS; EEG; ENCEPHALOPATHY; MORTALITY; CONSCIOUSNESS; POPULATION; SEIZURES